DESIGN AND DEVELOPMENT OF USEFUL ITEM DONATION APPLICATIONS WITH SCRUM METHOD - Mangapul Siahaan; Ariq Bimantoro (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Along with the rapid development of technology, it has changed people’s mindsets and lifestyles, starting from how to interact, learn, shop, to make donations to people who are in need. Donations do not always have to be in form of money, but can also be given in other forms such as clothing, equipment, and food. With the presence of internet technology, donations can be made online, which can be accessed via the web to mobile applications. This study will discuss the design and development of mobile-based applications of useful item donations. This research will use the scrum framework method which has 6 stages such as product backlog, sprint planning, sprint backlog, daily scrum, sprint review, and sprint retrospective. The result of this study is a mobile-based application where anyone can receive and give donations to each other.